Music learning and teaching in infancy, childhood, and adolescence an Oxford handbook of music education - McPherson, Gary.; Welch, Graham (Graham F.). (New York Oxford University Press, 2018)
"Music Learning and Teaching in Infancy, Childhood, and Adolescence is one of five paperback books derived from the foundational two-volume Oxford Handbook of Music Education. Designed for music teachers, students, and scholars of music education, as well as educational administrators and policy makers, the second book in this set explores a broad array of key issues, concepts, and debates related to music learning and teaching in three phases of a child's development. The first section provides an expanded view of infancy and early childhood, embracing a key theme that most young children's early music-making is improvised and used to communicate with others and the self. These chapters demonstrate the importance of "motherese" or "parentese" to young children's overall development, the extraordinary diversity and richness of children's early musical engagement, and how this can be viewed as a resource for further learning. The second section is devoted to the learning and teaching of music during the middle years of childhood, when music is often a mandated part of the school curriculum. While recognizing the enormous cultural and national differences, chapters in this section give an overview of many varied and innovative forms of musical learning and teaching globally. The authors address issues related to the types of teachers who provide music instructions to children internationally, how they were educated and trained, and how various nations organize their curriculum in ways that provide children with access and opportunities to engage with music in the classroom.
The third section focuses on the musical experiences and development of adolescents aged 12 to 18. These chapters explore the role of music in the lives of young people-including how they use and relate to music, how music educators can best meet students' needs, and the types of musical engagement that can either empower or disempower students through involvement in school music."--Provided by publisher.
Includes bibliographical references (pages 330-331) and index.
Keywords: Music -- Instruction and study